KESIAPAN STAKEHOLDERS DALAM PENGEMBANGAN PARIWISATA BERBASIS BUDAYA LOKAL DI SULAWESI TENGGARA - La Ode Aris (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2016)
This article is part of a research entitled Tourism Development Model Based on Local Culture of Southeast Sulawesi Province which takes place in three (3) regions of Muna Regency, Konawe District and Wakatobi Regency. This paper focuses on the readiness of stakeholders in the development of local culture-based tourism in Southeast Sulawesi. This article describes the readiness of stakeholders in the development of tourism destinations based on local culture. During this time, the existing tourism only rely on the uniqueness and beauty of the resort itself without any attempt to create a cultural engineering that juxtaposing local culture with tourism. Thus the tourists are not just visiting enjoy the natural beauty of the resort but at the same time can enjoy and witness the art and cultural attractions that are the assets of the area where the tour is located. This research is qualitative. Methods of data collection in this study are observation method and interview method, while data analysis using qualitative data analysis. The results of this study show the readiness of various parties, namely the readiness of the artists, the readiness of the tourism office, the availability of infrastructure of the main roads in remote villages and the readiness of the local community in accepting tourists. Keywords: readiness, stakeholders, development, tourism, local culture